Barriers to dental service access for individuals with multiple sclerosis: a scoping review - Seyed Kian Haji Seyed Javadi; Aisan Nouri; Hadi Ghasemi (BMC Oral Health)
Abstract Background Accessing dental care presents a significant challenge for individuals with multiple sclerosis (MS), influenced by the diverse array of symptoms associated with the disease. Aim This study aimed to identify the challenges faced by people with MS (PwMS) when accessing dental health services. Method The Joanna Briggs Institute scoping review methodology was employed to identify challenges related to dental service utilization among individuals with MS, following the Population–Concept–Context (PCC) framework. A comprehensive search was conducted across Embase, PubMed, Scopus, Web of Science, and Google Scholar without date restrictions. Thematic analysis was carried out using the Braun and Clarke approach, including coding, grouping subthemes, and identifying overarching theme Result Out of 172 articles searched, only three met the inclusion criteria. Challenges extracted from these articles were categorized into 4 main themes and 8 subthemes as follows: intrapersonal (comprising lack of information, manifestation of MS and fear), interpersonal (covering interactions between dental staff and MS patients, systemic interactions and support needs), structural (addressing physical and transportation barriers) and financial. Conclusion PwMS face significant challenges accessing dental services. Enhancing wheelchair accessibility, improving government financial support and upgrading public transportation can notably improve service accessibility. Additionally, educating dental staff and implementing specialized training for dental students can enhance their readiness to provide effective care for PwMS.